Factors Related To The Success Of Measles Immunization In Children Aged 2-3 Years - Jayanti, Resty; Puspita, Tika Noor; Pertiwi, Fenti Dewi; Alwi, Rizal; Fernanda, Tiara (Jurnal Kesehatan Manarang, 2024)
Providing immunizations to children can prevent and protect children from other dangerous and contagious infectious diseases, so that they will have the opportunity to take part in activities such as playing and studying. To determine the factors associated with the success of measles immunization in toddlers 2-3 years old in Loji Village. The location of this research was carried out in the working area of ​​the Pasir Mulya Community Health Center, precisely in Loji Village, West Bogor District, Bogor City, West Java 16118. This research was carried out from January 2023 to July 2023 with a time span of around 7 months. This type of research uses quantitative methods. This study used cross-sectional or cross-sectional. The sampling technique used was a total sampling technique with a sample size of 70 samples. The research instrument this time used by the researcher was a questionnaire. This bivariate analysis uses the Chi-square test. The educational level of parents, type of work, and the role of health workers and posyandu cadres can influence the success of measles immunization in toddlers 2-3 years old with respective p values ​​(0.004; 0.006; 0.014; 0.008). Therefore, it is important to increase public awareness and participation in immunization programs in order to achieve optimal targets. In conclusion, socio-economic factors and the role of health workers greatly influence the success of measles immunization in toddlers 2-3 years old, so there needs to be collaborative efforts between the government, community and health workers to increase immunization coverage.